Performance Status e a assistência odontológica hospitalar em oncologia - Costa, José Ricardo Sousa (2011)
The aim of the present study was to verify the prevalence of oral alterations in oncologic patients that had underwent hospital care, according to their general clinical conditions, which were measured by the Performance Status (PS) ECOG score. Another proposal was that this analysis would subsidize the creation of the dental protocols for the prevention, care and management of these oral alterations in a specific group of individuals. The prospective and observational study was performed in a period of six months, and consisted by weekly exams of the patients with oral neoplasms through the individual Performance Status ECOG scores and the identifications of the occurrence of oral alterations related to oral cancer and its treatment in each level. Fifty-four patients were examined and classified in PS 1 (185%), PS 2 (27.77%), PS 3 (59.26%), and PS 4 (33.33%). It was observed level changes in some individuals. The oral conditions were xerostomia (41.54%), dysgeusia (4.62%), oral ulcers (16.92%), mucositis (3.08%), haemostatic disturbances (15.38%), and infections (12.31%). Based on our findings, this study suggested that the presence of oral conditions were directly proportional to the PS ECOG levels and that this association providing conditions to create dental care programs characterized by the significant equity among the oncologic patients undergoing intensive care